Emotional Intelligence and Motivation in Learning English of Senior High School Students - stepani_tesya_yudhi_astari; Zsuzsa , Kaló; Lakatos, Kristóf (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study explores the relationship between emotional intelligence and English learning motivation in high school students in Metro City, Lampung. This study uses a quantitative design with a correlational approach. Data were collected through a questionnaire adapted from the Trait Emotional Intelligence Questionnaire (TEIQue) and Gardner's Attitude and Motivation Test Battery (AMTB) to measure emotional intelligence and intrinsic and extrinsic motivation. The sample of this study involved more than 300 students from several public and private high schools in Metro City who were selected randomly. The results of the analysis show that emotional intelligence has a significant positive relationship with extrinsic motivation (63%), but does not significantly affect motivation, with a negative contribution of -11%. In contrast, extrinsic motivation has a very strong influence on the intrinsic motivation of 94%. The instruments used in this study showed sufficient validity and reliability, although the convergent validity for the intrinsic motivation instrument still requires further development. This study provides important insights for educators to pay attention to extrinsic motivation factors in supporting English learning, as well as the importance of an individual approach to improving the balance between intrinsic and extrinsic motivation.